2021
DOI: 10.17309/tmfv.2021.2.09
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of Physical Loads in Female Students of Different Motor Ages

Abstract: Purpose: To develop and evaluate the impact of a program of sectional recreational aerobics classes, taking into account the differentiation of physical loads in female students of different motor ages. Materials and Methods. Participants: In the ascertaining experiment, 145 second-year female students were examined, in the formative experiment – 42 female students. The following indicators were measured: biological age (years) using V. P. Voitenko’s method (1991), motor age (years) and the general… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…In the course of their study, Bakanova (2011), Podrigalo, Prusik, Krzysztof, andPrusik, Katarzyna (2012) observed insufficient motor activity and mental strain in young people. Decreased physical activity and motivation to exercise in adults, as well as children and young people is a global phenomenon (Sigmundová, Chmelík, Sigmund, Feltlová & Frömel, 2013;Cachón-Zagalaz, Sánchez-Zafra, Lara-Sánchez, Zagalaz-Sánchez, & Shmatkov, 2020;Doroshenko et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…In the course of their study, Bakanova (2011), Podrigalo, Prusik, Krzysztof, andPrusik, Katarzyna (2012) observed insufficient motor activity and mental strain in young people. Decreased physical activity and motivation to exercise in adults, as well as children and young people is a global phenomenon (Sigmundová, Chmelík, Sigmund, Feltlová & Frömel, 2013;Cachón-Zagalaz, Sánchez-Zafra, Lara-Sánchez, Zagalaz-Sánchez, & Shmatkov, 2020;Doroshenko et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…However, there is a trend towards a decrease in the level of students' health. This is due to a decrease in the level of physical activity (Doroshenko et al, 2021). Currently, the attention of researchers is riveted to identifying the level of physical fitness and the state of health of students (Petruk & Grygus, 2019).…”
Section: Introductionmentioning
confidence: 99%